An examination of the relationship between careerism and organizational commitment, satisfaction, and performance. Issue 8 (18th December 2019) - Jain, Ajay K.; Sullivan, Sherry
Abstract : Purpose: Using psychological contract theory as its foundation, the purpose of this paper is to examine the important, but under-explored, relationship between careerism and organizational attitudes among workers in India. Design/methodology/approach: In total, 250 middle-level executives, working in six manufacturing plants of motorbike companies located in Northern India, were surveyed. Findings: As hypothesized, careerism was found to be negatively related to affective commitment, organization satisfaction and perceived organizational performance. Contrary to expectations, however, careerism was positively related to continuance and normative commitment. Research limitations/implications: The study is based on a cross-sectional survey. Also, because the motorbike industry is male dominated, all the executives surveyed are men. Practical implications: Despite concerns that employees with more transactional relationships with their employers are no longer loyal to their organizations, this study demonstrates that Indian employees with a higher careerism also have higher levels of normative and continuance organizational commitment. Originality/value: Prior research has produced conflicting results as to whether employees with more careerist, transactional psychological contracts with their employers have more negative organizational attitudes. This study contributes to research on psychological contract theory and careerism in today's turbulent career landscape while also answering calls to examine the generalizability of western theories of careers in non-western countries.